2015
DOI: 10.1016/j.conengprac.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Statistical process monitoring of a multiphase flow facility

Abstract: a b s t r a c tIndustrial needs are evolving fast towards more flexible manufacture schemes. As a consequence, it is often required to adapt the plant production to the demand, which can be volatile depending on the application. This is why it is important to develop tools that can monitor the condition of the process working under varying operational conditions. Canonical Variate Analysis (CVA) is a multivariate data driven methodology which has been demonstrated to be superior to other methods, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 215 publications
(78 citation statements)
references
References 35 publications
1
77
0
Order By: Relevance
“…The results presented in [15] demonstrated that CVA can effectively detect and diagnose faults in real complex systems working under varying operating conditions. The methodology presented in this investigation goes one step further to demonstrate that CVA can also be used for system identification in a large and complex real facility.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The results presented in [15] demonstrated that CVA can effectively detect and diagnose faults in real complex systems working under varying operating conditions. The methodology presented in this investigation goes one step further to demonstrate that CVA can also be used for system identification in a large and complex real facility.…”
Section: Resultsmentioning
confidence: 92%
“…These data are also necessary to build a dynamic model of the healthy process (2.2). The procedure used in this investigation to apply the CVA for fault detection and diagnosis is similar to the methodology used in [15], where CVA was used to detect and diagnose process faults in the same test rig used here. Three training data sets (T1, T2 and T3) were acquired from the system.…”
Section: Normal Operationmentioning
confidence: 99%
See 3 more Smart Citations